DETERMINAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PERAWAT RAWAT INAP RUMAH SAKIT MARINIR CILANDAK DI MASA PANDEMI COVID-19 TAHUN 2021 - Shela Ayu Melina (2022)
The use of PPE for nurses in hospitals is one of the efforts to implement health protocols during the COVID-19 pandemic to minimize the risk of transmission of the COVID-19 virus. Factors that can affect the compliance with the use of PPE in nurses include age, knowledge, attitudes, availability of Personal Protective Equipment (PPE), and social support. This study aims to determine the relationship between of age, knowledge, attitude, availability of PPE, and social support for compliance with the use of PPE in Inpatient Nurses at the Cilandak Marine Hospital during the COVID-19 pandemic in 2021. This research was a quantitative- analytical study, using a cross-sectional approach. The population in this study were 100 nurses and there was 51 nurses as samples by using purposive sampling technique. This research was conducted from October until December 2021. Data were analyzed by using a Chi-square test. It has been found that 33 of 51 nurses (64.7%) showed a high level of compliance to PPE use. The results of the analysis on statistical tests showed that availability of PPE (P-value = 0.015; POR = 5,625; 95% CI = 1,559 - 20,298) and social support (P-value = 0.031; POR = 0,031; 95% CI = 1,301 - 15,909) had a significant relationship to compliance with the use of PPE, with Therefore, consistency is needed on the hospital side in conducting socialization or training regarding OHS programs, especially related to the use of special PPE for handling COVID-19.